Chimpanzee‐red colobus encounter rates show a red colobus population decline associated with predation by chimpanzees at Ngogo. Issue 9 (17th June 2013) - Watts, David P.; Amsler, Sylvia J.
Abstract Chimpanzees (Pan troglodytes) hunt various primates, but concentrate on red colobus monkeys (Piliocolobus spp.) wherever the two species are sympatric. The extraordinarily large Ngogo chimpanzee community in Kibale National Park, Uganda, preys heavily on the local population of red colobus (P. tephrosceles). Census data showed a steep decline in this population in the center of the chimpanzees' home range between 1975 and 2007 [Lwanga et al., 2011; Teelen, 2007b]. Given no obvious change in food availability, predation by chimpanzees was the most likely cause [ibid.; Teelen, 2008]. However, census data from other parts of the home range raised the possibility that the decline was restricted to this central area [Teelen, 2007a] We present data from 1998 to 2012 on the rate of encounters between chimpanzees and red colobus that provide a chimpanzee‐centered estimate of red colobus density, thus of predation opportunities, throughout the home range. These corroborate census data by showing a long‐term decline in encounters near the center. They also show that encounters become relatively more common at increasing distances from the center, but encounter rates have decreased even in peripheral areas and, by implication, the red colobus population has declined throughout the study area. These data corroborate Teelen's [2008] conclusion that chimpanzee predation on red colobus during the 1990s and early 2000s was unsustainable. Hunting rates and prey offtake rates have also declined markedly; whether this will allow the red colobus population to recover is unknown. In contrast, rates at which chimpanzees encountered redtail monkeys (Cercopithecus ascanius) and grey‐cheeked mangabeys (Lophocebus albigena) did not decrease. Neither did they increase, however, contrary to long‐term census data from the center of the study area [Lwanga et al., 2011]. Am. J. Primatol. 75:927–937, 2013. © 2013 Wiley Periodicals, Inc.